2015
DOI: 10.4049/jimmunol.1402986
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Enhances Host Tolerance to Candida albicans Kidney Infections through Induction of IL-13 Production by CD4+ T Cells

Abstract: Susceptibility to systemic Candida albicans infection is determined by immune resistance, as well as by the ability to control Candida-induced immunopathologies. We showed previously that exogenous IL-33 can increase resistance to peritoneal C. albicans infection by regulating multiple steps of the neutrophil anti-Candida response. In this study, using a mouse model of systemic candidiasis, we observed that IL-33 administration limited fungal burden and inflammation and increased survival. In kidneys, IL-33 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…However, IL-33 also plays deleterious roles during Cryptococcus neoformans -induced lung mycosis and allergic inflammation in the lungs [ 42 , 43 ]. Research concerning the role of IL-33 in kidney infection is relatively limited, and a few reports are focused on cisplatin or Candida albicans -induced renal injury [ 13 , 44 ]. Our data demonstrate that infection with O .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IL-33 also plays deleterious roles during Cryptococcus neoformans -induced lung mycosis and allergic inflammation in the lungs [ 42 , 43 ]. Research concerning the role of IL-33 in kidney infection is relatively limited, and a few reports are focused on cisplatin or Candida albicans -induced renal injury [ 13 , 44 ]. Our data demonstrate that infection with O .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IL-33 deficiency or exogenous rIL-33 did not drastically change type 1 or type 2 cytokine expression during Orientia infection, as reported in a C . albicans -induced renal injury model [ 44 ]. While IL-33 did not reprogram type 1 vs. type 2 responses during Orientia infection, the IL-33/ST2 signaling significantly amplified the magnitude of pro-inflammatory responses ( Fig 3 ), cellular apoptosis, EC stress and activation, and host death (Figs 4 – 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tran et al reported that IL-33 administration enhanced fungal clearance by increasing the phagocytosis activity of neutrophils. Moreover, deletion of IL13 abolished IL-33-mediated polarization of M2 macrophages and renal functional recovery [48]. This study indicates that therapeutic IL-33 may benefit patients with systemic candidiasis [42].…”
Section: Il-33 In Acute Kidney Injurymentioning
confidence: 95%
“…Endothelial cells [47], cardiomyocytes [26], CD4 + T cells [27], macrophages [48], neutrophils, iNKT cells, and ILC2 cells [49,50] were shown to respond to IL-33 activation through their membrane receptor ST2L. The expression of ST2L or IL-33-responsiveness in tubular epithelial cells (including proximal tubular cells, distal tubular cells, collecting duct cells, and pelvic urothelium), mesangial cells or podocytes has not been fully investigated or reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they demonstrated that mice were more resistant when they were adoptively transferred with M2 macrophages, as evidenced with lower kidney fungal burdens, renal pro-inflammatory cytokines production (i.e. IL6, TNFα and IL1β) and serum creatinine levels [109]. Hence, a thorough investigation on CD169 + macrophages will certainly facilitate a more detailed understanding of Candida immunity.…”
Section: Considering That the Presence Of Neutrophils During The Initmentioning
confidence: 99%